THE USE OF SHOW AND TELL METHOD TO IMPROVE STUDENTS SPEAKING ABILITY - Rahayu, Arum (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2023)
This study examines the application of the Show and Tell learning method on the "Who People Are" Material in improving the Speaking Skills of second-semester students of the Islamic Education Study Program of STAI Ma'arif Magetan. The approach used is a qualitative approach and the type of research is Classroom Action Research (CAR). The data analysis technique used is the qualitative data analysis technique. This research was conducted in May-June 2023 with 32 students. Based on data obtained during the implementation of Cycle I and Cycle II that the results of research in Cycle I showed sufficient categories, and there was a rapid increase in Cycle II which showed good categories and achieved predetermined indicators. The conclusion of this study stated that the application of the Show and tell learning method in the "Who People Are" Material was working well in improving the Speaking Skills of second-semester students of the Islamic Education Study Program STAI Ma'arif Magetan.